Model-free reconfiguration mechanism for fault tolerance - Jain, Tushar; Yamé, Joseph J.; Sauter, Dominique (Zielona Góra: Uniwersytet Zielonogórski)
The problem of fault tolerant control is studied from the behavioral point of view. In this mathematical framework, the concept of interconnection among the variables describing the system is a key point. The problem is that the behavior we intend to control is not known. Therefore, we are interested in designing a fault accommodation scheme for an unknown behavior through an appropriate behavioral interconnection.
Keywords: fault tolerant control; control performance; behavioral theory; switching control